2013
DOI: 10.4304/jcp.8.4.896-903
|View full text |Cite
|
Sign up to set email alerts
|

Research on Real-time Simulation and Control of Linear 1-stage Inverted Pendulum

Abstract: Inverted pendulum system is a complex, unstable and nonlinear system. In order to make it become an adaptive and robust stable system in control strategy, the mathematical model of linear l-stage inverted pendulum has been established by means of Newton mechanics. The control strategies including classic control methods and modern control methods, such as the PID control algorithm, the pole assignment algorithm and the T-S fuzzy control algorithm.The real-time control results show that the PID control algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…Correspondingly, the modern control theory controllers are idealized to control nonlinear system and consume less time as compared to intelligent controllers. Song et al [7] studied the comparison between PID (Proportional-Integrate-Derivative), pole placement and fuzzy logic controller to control the stabilization problem of cart pendulum system. They concluded that the pole placement controllers give better dynamic and steadystate performance as compared to other two controllers.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the modern control theory controllers are idealized to control nonlinear system and consume less time as compared to intelligent controllers. Song et al [7] studied the comparison between PID (Proportional-Integrate-Derivative), pole placement and fuzzy logic controller to control the stabilization problem of cart pendulum system. They concluded that the pole placement controllers give better dynamic and steadystate performance as compared to other two controllers.…”
Section: Introductionmentioning
confidence: 99%
“…The modelling techniques based on FIS are appealing and have found many successful applications in various fields including Fuzzy PID position control approach in computer numerical control machine tool ; research on real-time simulation and control of linear 1-stage inverted pendulum (Song, 2013); as well as on a study on the control methods based on 3-DOF helicopter model (Gao, 2012;Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The control method has a wide range of uses in the field of military industry, aerospace science and technology, robot and general industrial process. In recent years, many scholars have used the classical control theory, modern control theory and a variety of intelligent control methods [1,2]in this system and successfully achieved stability control of inverted pendulum system.…”
Section: Introductionmentioning
confidence: 99%